Chemistry of lignin-based materials. Issue 3 (1st September 2013) - Chung, Hoyong; Washburn, Newell R.
Abstract : There is a need for renewable resources as a raw material for commodity polymers. Lignin is one of the most important natural biopolymers from renewable resources due to its sufficient supply, robust material properties and the fact that its use does not compete with the food supply. Lignin has been investigated since the late 19th century, but its applications are limited due to poor processability, low reactivity and intrinsic heterogeneity depending on the plant source and isolation methods used. Current strategies for using lignin in modern materials center on integrating it with other natural or synthetic polymers. This review article introduces the technological importance of lignin and focuses on copolymers and blends based on lignin in a broad range of applications.